Corporate environmental governance of banks in Malaysia: unveiling the support-based practices - Azri Zunurane, Muhammad; Sufiawati Khairani, Noor; Najuna Misman, Faridah (International Journal of Engineering and Technology, 2018)
This study investigates the support-based Corporate Environmental Governance (CEG) practices of banks in Malaysia. Proponents of CEG practices highlighted that understanding the CEG practices permits banks to realize its role in promoting sustainable development while at the same time gaining financial advantages and reducing negative impacts to the natural environment. However, few researchers concentrates on the support-based CEG practices, especially among the Malaysian banks, the focus of this study. This paper thus contributes in addressing this literature gap by focusing on the support-based CEG practices of banks in Malaysia. The study adopts content analysis technique in obtaining data from the latest sustainability report and official website of the banks in Malaysia. The findings reveal six types of support-based CEG practices implemented by the Malaysian banks. Furthermore, consistent with the literature, the findings also indicate energy conservation as the most implemented support-based CEG practices. Â